2022
DOI: 10.1088/2631-7990/ac9652
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic atomization minimum quantity lubrication machining: from mechanism to application

Abstract: Metal cutting fluids in flood condition does not meet the urgent needs of emission cutting and carbon reduction, minimum quantity lubrication (MQL) is an effective alternative to flood lubrication. Nevertheless, the micro-droplets produced by pneumatic atomization MQL have poor infiltration and wetting properties, which cannot fully exert the film-forming and heat transfer performance of lubricant. The unique empowering mechanism of electrostatic atomization can not only solve the above technical bottleneck, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(27 citation statements)
references
References 284 publications
(320 reference statements)
0
22
0
Order By: Relevance
“…It is observed that the average deviation of our data with other works is less than 6%. Validation of computational studies have been done in several previous works [45][46][47][48][49][50][51][52][53][54][55] Figure 4 displays the flow stream and concentration of the coolant gas (He and CO 2 ) for injection system released from the tip of disk located on the spike. As expected, the formation of the circulations in the cavity is main flow physic of the proposed configurations.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the average deviation of our data with other works is less than 6%. Validation of computational studies have been done in several previous works [45][46][47][48][49][50][51][52][53][54][55] Figure 4 displays the flow stream and concentration of the coolant gas (He and CO 2 ) for injection system released from the tip of disk located on the spike. As expected, the formation of the circulations in the cavity is main flow physic of the proposed configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Since the fabrication of graphene, which consists of one or more graphite layers with SP 2 allotrope bonds of 2D carbon. 112–117 Due to its excellent properties such as thermal conductivity 117–125 and electrical conductivity, 126–131 high charge density, 132 mobility, 133 optical conductivity 134 and mechanical properties, 135 it has become a unique material. The main building blocks of carbon nanostructures are a graphite layer with SP 2 bonding covalently functionalized carbon atoms in a hexagonal honeycomb network (Fig.…”
Section: Graphenementioning
confidence: 99%
“…27,[100][101][102] Some of the important properties of graphene that have been reported so far include large surface to weight ratio (for example, 1 gram of graphene can cover several football elds), approximate elasticity of 1100 GPa, 103,104 fracture toughness of 125 GPa, 103,104 high thermal conductivity and high surface area (2630 m 2 g −1 ) [105][106][107][108][109][110][111] Since the fabrication of graphene, which consists of one or more graphite layers with SP 2 allotrope bonds of 2D carbon. [112][113][114][115][116][117] Due to its excellent properties such as thermal conductivity [117][118][119][120][121][122][123][124][125] and electrical conductivity, [126][127][128][129][130][131] high charge density, 132 mobility, 133 optical conductivity 134 and mechanical properties, 135 it has become a unique material. The main building blocks of carbon nanostructures are a graphite layer with SP 2 bonding covalently functionalized carbon atoms in a hexagonal honeycomb network (Fig.…”
Section: Physical Properties Of Graphenementioning
confidence: 99%
“…[53][54][55][56][57][107][108][109][110][111] Biomarkers can be proteins, mutated DNA, RNA, lipids, carbohydrates, and small molecules resulting from cellular metabolism. [58][59][60][112][113][114][115][116][117][118] Table 1 exemplies some of these biomarkers. 14…”
Section: Introductionmentioning
confidence: 99%